Working effectively with asset managers and institutional groups. Issue 4 (15th August 2016) - Read, Dustin C; Hopkins, Erin; Goss, Rosemary Carruci
Abstract : Purpose: This paper examines how property management firms are responding to the demands of asset managers and institutional real estate owners to address potential sources of conflict related to fee structures, reporting requirements and incongruent managerial philosophies. Design/methodology/approach: Interviews conducted with executives representing 25 of the largest apartment management firms in the United States are used to complete the analysis. Findings: Many of the apartment management firms represented in the sample are embracing incentive-based fee structures and a la carte service offerings as a means of aligning their interests with those of the asset managers and institutional clients they represent. A number of these firms are additionally incorporating new technologies and training procedures into their operating platforms to facilitate customization and responsiveness throughout the reporting process. Respondents also noted their firms are becoming more selective about who they work with and more willing to walk away from business opportunities when managerial philosophies conflicts. Research limitations/implications: The characteristics of the population from which the sample is drawn limit the generalizability of the results to large property management firms operating in the multifamily housing industry. Nonetheless, the best practices put forth by those participating in the study are anticipated to have relevance to a wide variety of real estate practitioners. Practical implications: The analysis links theory to practice by considering how apartment managers are evolving in response to the institutionalization of the multifamily housing industry. Originality/value: This paper is the first to the authors' knowledge to examine apartment managers' perceptions about the challenges associated with representing institutional clients.